2009
DOI: 10.1002/adma.200800423
|View full text |Cite
|
Sign up to set email alerts
|

Ga2Te3Sb5—A Candidate for Fast and Ultralong Retention Phase‐Change Memory

Abstract: Incongruent melting phenomenon shows the feasibility of multilevel control using the phase‐change material Ga2Te3Sb5 (Ga‐TS). Electrical results showed that Ga‐TS cells require 25% less RESET current than do GST cells. Meanwhile it possesses a high programming speed, ultralong data retention extrapolated to one million years at 120 °C, and superior thermal properties for phase‐change random‐access‐memory applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…Growth-dominated crystallization mechanism of PCL could be responsible for the ultra-fast switching speed. [15][16][17] It is also shown that the SLEbased PCRAM has smaller value of set voltage than the CEbased one at the pulse width of 5 ns, further suggesting lower power of the SLE-based PCRAM.…”
Section: B)mentioning
confidence: 84%
See 1 more Smart Citation
“…Growth-dominated crystallization mechanism of PCL could be responsible for the ultra-fast switching speed. [15][16][17] It is also shown that the SLEbased PCRAM has smaller value of set voltage than the CEbased one at the pulse width of 5 ns, further suggesting lower power of the SLE-based PCRAM.…”
Section: B)mentioning
confidence: 84%
“…The top electrode fabricated alternately by TiN and W layers was embedded in PCRAM to achieve low power. Since Ga-Sb-Te ternary materials show fast speed and brilliant data retention in comparison with those of widely used Ge 2 Sb 2 Te 5 (GST), 15,16 it is used as a PCL for PCRAM in this study.…”
mentioning
confidence: 99%
“…The Ga 4 Sb 6 Te 3 ͑E͒ also performs at fast speed comparable to Ga 2 Sb 5 Te 3 ͑C͒, which has been demonstrated to have fast set performance ͑ϳ20 ns͒ and very long data retention for phase-change memory. 9 It is also indicated that by raising the Sb/Te atomic ratio ͑from 1.22 to 1.95͒ with GaSb incorporation the crystallization speed can be further increased while the low Sb/Te ratio ͑0.79͒ material is the slowest. Similar results were demonstrated for In doped Sb-Te phase-change material.…”
Section: The Crystallization Behavior Of Stoichiometric and Off-stoicmentioning
confidence: 97%
“…Moreover, the thermal cross-talk between neighboring cells which will be more severe in high-density memory arrays requires higher stability of the amorphous phase to boost data retention performances of PCM [1]. What is more, there are also other issues such as the high reset current and slow speed of amorphous-to-crystalline phase transition that need to be addressed [10][11][12]. Thermal stability and transformation speed are two main features that can be further improved for practical applications of PCM [13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Chalcogenide materials, such as Ge 2 Sb 2 Te 5 (GST), have been widely studied and utilized for PCM applications due to its excellent overall performances [5,6]. However, GST has a low crystallization temperature (about 150 C [6,7]), which leads to poor data retention just sufficient for some consumer applications (85 C for 10 years [8,9]), far away from the requirements of automotive system (120 C for10 years [10]). Moreover, the thermal cross-talk between neighboring cells which will be more severe in high-density memory arrays requires higher stability of the amorphous phase to boost data retention performances of PCM [1].…”
Section: Introductionmentioning
confidence: 99%